RE2[B2(SO4)6] (RE = Y, La–Nd, Sm, Eu, Tb–Lu): a silicate-analogous host structure with weak coordination behaviour. Issue 13 (13th March 2019) - Netzsch, Philip; Hämmer, Matthias; Gross, Peter; Bariss, Harijs; Block, Theresa; Heletta, Lukas; Pöttgen, Rainer; Bruns, Jörn; Huppertz, Hubert; Höppe, Henning A.
Abstract : The very first thorough investigation of the rare earth borosulfates RE 2 [B2 (SO4 )6 ] with RE = Y, La–Nd, Sm, Eu and Tb–Lu focusses on synthetic aspects and especially optical properties. Abstract : The rare earth borosulfates RE 2 [B2 (SO4 )6 ] with RE = Y, La–Nd, Sm, Eu and Tb–Lu were synthesised under solvothermal conditions starting from the metal chlorides (Pr, Nd, Eu), the metal oxides (Y, La, Ce, Sm, Tb, Dy, Er, Tm, Lu), or the metal powders (Ho, Yb). They crystallize isotypically with Gd2 [B2 (SO4 )6 ] in space group C 2/ c ( Z = 4, a = 1346.9(3)–1379.24(17) pm, b = 1136.4(3)–1158.87(14) pm, c = 1079.9(3)–1139.54(14) pm, β = 93.369(8)–93.611(4)°). The anionic structure consists of an open-branched vierer single ring oB, 1 r [B2 S2 O12 (SO3 )4 ] 6−, similar to the mineral eakerite (Ca2 Al2 Sn[Si6 O18 ](OH)2 ·2H2 O) which contains oB, 1 r [Si4 O12 (SiO3 )2 ] 12− moieties. The fluorescence spectroscopy of the samples with RE = Ce, Eu and Tb features emissions in the deep UV, the red, and the green part of the spectrum and furthermore revealed a weak coordination behaviour of the borosulfate anion. Thermal analysis of Eu2 [B2 (SO4 )6 ] showed the highest thermal stability observed for borosulfates so far; respective trends within the borosulfate family are discussed. Additionally, the compounds were characterised by magnetic measurements, vibrational and 151 Eu Mößbauer spectroscopy.